Evaluation of rotary fluidized-bed as a wet granulation equipment - (:unkn) unknown (MEDPHARM GMBH SCIENTIFIC PUBL, 1995)
Rotary fluidized-bed (RFB) was evaluated using a Box-Behnken design. Theophylline was used as a model drug at 0.1, 1.0. and 10.0% levels in combination with lactose, starch and Avicel(R). The powder and tablet forms were analysed for drug content (DC). The powder showed a relative standard deviation (RSD) of 2.68 - 89.75%; tablets provided a RSD of 0.65 - 4.17% for the mean theophylline content. The effect of drug level and the rotor speed of the REB were found to be significant on the RSD. The effect of drug ratio was found to be the only significant factor on DC. The tapped density of granules was found to be dependent on the excipient type. The statistical mean granule size, as a function of time, was successfully predicted by fitting the data to a second order equation. The RFB was found to be a promising machine to perform wet granulation for tabletting.
Keywords: rotary fluidized-bed; wet granulation; content uniformity; box-Behnken design; response surface methodology